Baldwin’s “Sonny’s Blues”: An Historical Story of Double-Consciousness and Its Relevance in Today’s America - Sherma, Amar Bahadur (THE ACADEMIA, 2025)
This article explores James Baldwin’s short story “Sonny’s Blues” is one of the best examples of how African-Americans are sandwiched between two warring ideas— double-consciousness. This essay examines the story through Du Bois’ theoretical framework of double-consciousness. His theory is an idea of being one person with two identities owing to the clash between oppressive and dominated societies. The ideology of double-consciousness is reinforced in the story through the thoughts and action of two brothers: Sony and his unnamed brother (narrator). These two brothers view the world differently and adopt different approaches to life. Sony intends to essentialize their ancestral norms through music, whereas his brother wishes to secure a better life by assimilating into the world dominated by whites. The story is often analyzed under the lens of racial tensions, brotherly ego, classism, slavery, family reunion, and many more themes. After analyzing “Sonny’s Blues” as the primary text and drawing on other scholarly articles, the article has discovered that different vocations can serve for people with double identities as an outlet for expressing their traumatic experiences and other elements such as mutual respect, inclusiveness, and empathy can foster a better society to live in.